Leading Sector in Banyumas Regency During The Covid-19 Pandemic Using Location Quotient and Shift-Share - Suprih Handayani; Lilis Siti Badriah; Suharno Suharno; Dwi Asih Septi Wahyuni; James Sinurat (Future Science, 2022)
The economic growth rate is an indicator used to measure the achievement of development. In 2020, the economic growth rate of Banyumas Regency contracted by -1.65 percent but this figure is still above the economic growth rate of Central Java Province which is -2.65 percent. The economic growth of a region is driven by the leading sectors in the region. This research aims to find out the leading sectors in Banyumas Regency that experienced progressive, growing, sluggish and backward movement during the Covid-19 outbreak compared to Central Java Province using Location Quotient and Shift-Share (LQ Shift- Share) analysis. The results of the analysis showed that the sectors that contributed the two largest to the Gross Regional Domestic Product (GRDP) in Banyumas Regency in 2020 at the same time including the progressive sector were trade sector (G) and construction sector(F).